Selective Laser Sintering Manufacturing and Characterization of Lightweight PA 12 Polymer Composites with Different Hollow Microsphere Additives - Kısasöz, Burçin Özbay; Serhatlı, İ. Ersin; Bulduk, M. Enes (Springer, 2021)
The use of additives in polyamide polymeric SLS built frameworks further reinforces the goal of developing lightweight components, which serves as the basis for the current investigation. In this paper, different amounts of hollow glass microspheres (HGMs) were added to polyamide 12 (PA 12), and their sintered components were compared for their physical and mechanical properties, including tensile and 3-point bending tests. In terms of density reduction, the PA 12-20HGM composite structure achieved the highest reduction figure of 20.8 %. According to specific strength and modulus calculations, PA 12-20HGS60 and PA 12-20HGM composite structures provided the highest mechanical test results.
Keywords: Additive manufacturing; Lightweight; Polymer composite; SLS